2020
DOI: 10.1007/s00586-020-06575-5
|View full text |Cite
|
Sign up to set email alerts
|

Physical activity and low back pain in children and adolescents: a systematic review

Abstract: Introduction Due to a high prevalence of low back pain (LBP) among children and adolescents, it is significant to seek effective prevention and therapeutic procedures. One idea for the programmes is a potential relation between the occurrence of LBP and the level of physical activity. The aim of this review was to analyse the current knowledge regarding the association between physical activity and LBP among children and adolescents. Methods Public… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
17
0
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 24 publications
(21 citation statements)
references
References 41 publications
(117 reference statements)
2
17
0
2
Order By: Relevance
“…With the advent of aging society, the prevalence and number of patients with LBP continue to increase globally; meanwhile, the incidence of LBP also displays a gradual increased trend in young people. It is reported that about 40% children aged from 9 to 18 years suffer from LBP ( Calvo-Muñoz et al, 2013 ; Kędra et al, 2021 ).…”
Section: Introductionmentioning
confidence: 99%
“…With the advent of aging society, the prevalence and number of patients with LBP continue to increase globally; meanwhile, the incidence of LBP also displays a gradual increased trend in young people. It is reported that about 40% children aged from 9 to 18 years suffer from LBP ( Calvo-Muñoz et al, 2013 ; Kędra et al, 2021 ).…”
Section: Introductionmentioning
confidence: 99%
“…Misclassifications and loss of in-depth information may also have occurred through dichotomisation of the variables. For example, both high and low physical activity levels have been associated with low back pain in previous research (Kędra et al, 2021). Through dichotomisation, a potential u-shaped relationship was not taken into account (Heneweer et al, 2009).…”
Section: Strengths and Limitationsmentioning
confidence: 99%
“…Sleep problems might increase the risk of pain in some body regions and subgroups, but not for musculoskeletal pain in general (Andreucci et al, 2017). For physical activity level, results from a systematic review of longitudinal and cross‐sectional studies indicated that both very high and very low activity levels were associated with low back pain in children and adolescents (Kędra et al, 2021). For alcohol consumption and future low back pain, the results from longitudinal studies are inconsistent (Hestbaek et al, 2006a; Smith et al, 2017), while there are few studies examining the association between other lifestyle behaviours in adolescence, such as diet and illicit drug use, and future musculoskeletal pain.…”
Section: Introductionmentioning
confidence: 99%
“…Although this increment is low, it is significant. There have been several studies addressing back pain and the lumbar lordosis, particularly low back pain [49][50][51], but the association with thoracic spine postural angle as a predictor of back pain has been little studied, except in more severe clinical conditions such as Scheuermann's disease [52,53].…”
Section: Back Pain and Balance Parametersmentioning
confidence: 99%